Experience of pharmacy involvement in a disaster simulation exercise within a pediatric hospital emergency department: A pilot project. (25th December 2021) - Marks, Kayla; Chung, Sarita; Li, Joyce; Waltzman, Mark; Manzi, Shannon; Shah, Dhara
Abstract: Purpose: In this descriptive report, we describe a unique trial of pharmacist participation in a multidisciplinary pediatric emergency department disaster simulation exercise. With the number of disasters increasing worldwide, the role of pharmacists in disaster response is of particular interest to the profession. Summary: This observational study describes pharmacist participation in a disaster simulation exercise. An evaluation tool was developed to assess participants' performance in the following domains: communication, pharmacotherapy, problem solving/decision making, and teamwork/organization. The observers used a rating scale of "concise/prompt, " "needs improvement, " or "not done" to evaluate performance on each objective. The participants' self-perceived knowledge of disaster response was assessed with pre- and postsimulation surveys using Likert scales. Five simulation exercises were held from June to October 2019, with 2 pharmacists participating in each simulation. Within the problem solving/decision making and communication domains, pharmacists were concise/prompt 66% of the time, while they were concise/prompt for 88.8% and 92.5% of tasks in the teamwork/organization and pharmacotherapy domains, respectively. Surveys of self-perceived knowledge revealed that while only 10% of pharmacists felt "moderately prepared" prior to the simulation exercise, 80% of pharmacists felt moderately prepared to care for patients during a disaster event after the simulation exercise. Conclusion: This report describes a unique approach of including emergency department–trained pharmacists in disaster simulation exercises to enhance their professional development, improve team dynamics in a mass casualty scenario, and increase their own reported level of preparedness to effectively manage a surge in critically ill pediatric patients.